Furuncular myiasis for the Western dermatologist: treatment in outpatient consultation. (31st October 2017) - Blaizot, Romain; Vanhecke, Christophe; Le Gall, Philippe; Duvignaud, Alexandre; Receveur, Marie‐Catherine; Malvy, Denis
Abstract: Background: Furuncular myiasis is likely to be seen by Western dermatologists because of the increasing number of international travelers but remains unfamiliar to most of them, who tend to refer these patients to hospitals. Different treatments have been proposed, but many of them are not achievable in outpatient consultation. Methods: We reported three typical cases of furuncular myiasis, according to each species involved, and proposed diagnostic and therapeutic guidelines for dermatologists in outpatient consultation. Results: One patient, complaining of an inflammatory nodule of the leg with a central punctum, was diagnosed with Dermatobia hominis infection, after a forest walk in French Guiana. One woman returned from Senegal with a nodule of the left buttock. She had been infected by a Cordylobia anthropophaga larva after drying her underwear under a mango tree. One woman living in Cameroon presented with scalp nodules, pain, fatigue, and facial edema. She had been infected by more than 40 larvae of Cordylobia rodhaini after drying her sheets under a mango tree. Manual extraction ensured complete healing in the three patients. We used neither doppler ultrasound nor occlusive dressing. Diagnosis was immediately made thanks to the typical clinical stories. Conclusions: The diagnosis of furuncular myiasis requires only clinical skills and basic knowledge of life cycles. The treatment varies slightly depending on the species involved but is achievable in outpatient consultation and does not require occlusive dressing.